1996
DOI: 10.1111/j.1476-5381.1996.tb15980.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidinoceptor‐mediated activation of phospholipase C and phospholipase A2 in RAW 264.7 macrophages

Abstract: Taiwan1 As well as the presence of P2Z purinoceptors previously found in macrophages, we identified pyrimidinoceptors in RAW 264.7 cells, which activate phospholipase C (PLC) and phospholipase A2 (PLA2).2 The relative potency of agonists to stimulate inositol phosphate (IP) formation and arachidonic acid (AA) release was UTP = UDP > > ATP, ATPyS, 2MeSATP. For both signalling pathways, the EC50 values for UTP and UDP (3 uiM) were significantly lower than that for ATP and all other analogues tested (> 100 yM).3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
21
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
6
21
0
Order By: Relevance
“…Previous studies have demonstrated that UTP, acting via pyrimidinoceptors, can stimulate phosphoinositide breakdown and increase intracellular Ca 2+ levels (20). Although UTP alone had no effect, UTP potentiated the LPS-induced NO production, activation of transcription factor NF-kB and iNOS expression in mouse J774 macrophages (21).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated that UTP, acting via pyrimidinoceptors, can stimulate phosphoinositide breakdown and increase intracellular Ca 2+ levels (20). Although UTP alone had no effect, UTP potentiated the LPS-induced NO production, activation of transcription factor NF-kB and iNOS expression in mouse J774 macrophages (21).…”
Section: Discussionmentioning
confidence: 90%
“…Because we previously characterized the UTP-triggered PI signaling cascades in RAW 264.7 cells (Lin and Lee, 1996), we explored the possible involvement of PI/PLC-triggered second messengers in the pH i decrease. With respect to PKC pathways, we found that 1 M phorbol-12-myristate-13-acetate, a PKC-activating phorbol ester, had no effect on pH i .…”
Section: Utp-induced Extracellular Camentioning
confidence: 99%
“…AA release was measured as described previously (Lin and Lee, 1996). In brief, cells were prelabeled with 0.3 Ci/ml [ 3 H]AA in DMEM for 24 hr at 37°and then washed twice with HEPES-buffered solution and incubated in HEPES solution containing 0.5% fatty acid-free bovine serum albumin before stimulation with UTP, thapsigargin, or ionomycin (1 M) at 37°for 30 min.…”
Section: Measurement Of [Camentioning
confidence: 99%
See 2 more Smart Citations